A Novel Polysaccharide From Chuanminshen violaceum and Its Protective Effect Against Myocardial Injury - He, Peng; Zhang, Mi; Zhao, Meng; Zhang, Mengyao; Ma, Benxu; Lv, Hongyu; Han, Yantao; Wu, Dingtao; Zhong, Zhangfeng; Zhao, Wenwen (Frontiers in Nutrition, 2022)
We isolated and purified a novel polysaccharide from the root of Chuanminshen violaceum, namely, Chuanminshen violaceumis polysaccharide (CVP) and confirmed its structure and molecular weight. Furthermore, in vivo experiment, CVP’s protective effect against myocardial ischemia-reperfusion (I/R) injury in mice was evidenced by significantly reducing I/R-induced myocardial infarction (MI) size, decreasing the secretion of heart damage biomarkers, and improving cardiac function. Then, the myocardial anoxia/reoxygenation (A/R) injury model was established to mimic reperfusion injury. Noticeably, ferroptosis was the major death manner for A/R-damaged H9c2 cells. Meanwhile, CVP significantly inhibited ferroptosis by decreasing intracellular Fe2+ level, enhancing GPX4 expression, and suppressing lipid peroxidation to confront A/R injury. In conclusion, CVP, with a clear structure, ameliorated I/R injury by inhibiting ferroptosis.